Kallikrein 8: A key sheddase to strengthen and stabilize neural plasticity. (September 2022) - Shiosaka, Sadao
Abstract: Neural networks are modified and reorganized throughout life, even in the matured brain. Synapses in the networks form, change, or disappear dynamically in the plasticity state. The pre- and postsynaptic signaling, transmission, and structural dynamics have been studied considerably well. However, not many studies have shed light on the events in the synaptic cleft and intercellular space. Neural activity-dependent protein shedding is a phenomenon in which (1) presynaptic excitation evokes secretion or activation of sheddases, (2) sheddases are involved not only in cleavage of membrane- or matrix-bound proteins but also in mechanical modulation of cell-to-cell connectivity, and (3) freed activity domains of protein factors play a role in receptor-mediated or non-mediated biological actions. Kallikrein 8/neuropsin (KLK8) is a kallikrein family serine protease rich in the mammalian limbic brain. Accumulated evidence has suggested that KLK8 is an important modulator of neural plasticity and consequently, cognition. Insufficiency, as well as excess of KLK8 may have detrimental effects on limbic functions. Highlights: Kallikrein 8 (KLK8) is an important modulator of neural plasticity, synaptic tagging, and consequently, cognition. Neural activity-dependent protein shedding by KLK8 is involved in mechanical modulation of cell-to-cell connectivity, and variety of receptor mediated or non-mediated biological actions. Insufficiency, as well as excess of KLK8 may cause detrimental effects on the limbic functions, and consequently, mental diseases such as Alzheimer's disease.